Proceedings of the 2nd Social and Humaniora Research Symposium (SoRes 2019) 2020
DOI: 10.2991/assehr.k.200225.095
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Educator Certification in Developing Pedagogy, Personality, Social and Professional Competencies

Abstract: According to UNDP, UNESCO, and GTCI reports, the quality of Indonesian education was still low, so that a joint effort (government, educational institutions and community) is required to improve the quality of education, such as participating in a program educational certificate. This research was conducted to recognize and understand the competency indicators of pedagogy, personality, social, and professional relating to certified teachers. Moreover, this research employed a qualitative method using a triangu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 14 publications
1
55
0
5
Order By: Relevance
“…Tutors as educators refer to Law Number 20 of 2003 Article 1 paragraph 6 which states that "educators are qualified education personnel as teachers, lecturers, counselors, tutors, instructors, facilitators, and other designations according to their specificity, and participate in providing education" (Undang-Undang RI 20, 2003). Educators are professionals in charge of planning and implementing the learning process, assessing learning outcomes, conducting guidance and training, as well as conducting research and community service, especially for educators at universities (Rusilowati and Wahyudi, 2020). As an educational staff, a tutor oversees carrying out administration, management, development, supervision, and technical services to support the educational process in the education unit (Hartinah et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tutors as educators refer to Law Number 20 of 2003 Article 1 paragraph 6 which states that "educators are qualified education personnel as teachers, lecturers, counselors, tutors, instructors, facilitators, and other designations according to their specificity, and participate in providing education" (Undang-Undang RI 20, 2003). Educators are professionals in charge of planning and implementing the learning process, assessing learning outcomes, conducting guidance and training, as well as conducting research and community service, especially for educators at universities (Rusilowati and Wahyudi, 2020). As an educational staff, a tutor oversees carrying out administration, management, development, supervision, and technical services to support the educational process in the education unit (Hartinah et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The principle of competence in a teacher is being able to appreciate the expertise of the subject being educated as the most important indicator. [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, if students fail to convey what they need, it can certainly be a problem for students and have an impact on their learning outcomes at school (Habibi et al, 2019). A study found that there is a positive and significant relationship between effective communication on student learning outcomes (Rusilowati & Wahyudi, 2020). Thus, if students lack the communication skills to interact with teachers and their friends at school, it can also negatively affect their learning outcomes.…”
Section: Introductionmentioning
confidence: 99%